A Knowledge-Based Simulated Annealing Algorithm to Multiple Satellites Mission Planning Problems. (27th November 2013) - Jin, Da-Wei; Xing, Li-Ning
Abstract : The multiple satellites mission planning is a complex combination optimization problem. A knowledge-based simulated annealing algorithm is proposed to the multiple satellites mission planning problems. The experimental results suggest that the proposed algorithm is effective to the given problem. The knowledge-based simulated annealing method will provide a useful reference for the improvement of existing optimization approaches.